Pengaruh Kebijakan Dividen Terhadap Harga Saham Pada Perusahaan Manufaktur di Bursa Efek Indonesia (BEI) - Humera Asad Ullah Khan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study was conducted to determine the effect of dividend policy on stock prices of manufacturing companies listed on the Indonesia Stock Exchange during 2024. The type of research used in this study is a quantitative ratio analysis technique with a descriptive approach. The sampling technique is purposive sampling using the documentation method obtained from the financial statements of each company. The results of this study indicate that dividend policy has a positive and significant effect on stock prices. The benefits of this study for company management can be used as a consideration regarding matters related to the influence of variables on dividend.